Composition for glass, photovoltaic glass and solar cell

By using specific combinations of glass compositions in photovoltaic glass and adjusting component content and matching, the problem that the existing float production lines cannot meet the requirements of high light transmittance and mechanical strength of photovoltaic glass is solved, and the effect of efficient preparation of ultra-white float glass is achieved.

CN119638196APending Publication Date: 2025-03-18ZHAOHONG PRECISION (BEIJING) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411492281.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing ordinary float production lines cannot meet the high light transmittance and mechanical strength requirements of photovoltaic glass, especially the inability to effectively produce ultra-white float glass.

Method used

Specific glass compositions, including silica, alumina, magnesium oxide, calcium oxide, iron oxide, sodium oxide, potassium oxide, sulfur trioxide and rare earth oxide, are used to improve the overall refractive index and optical properties of the glass by adjusting the content and combination of these components.

Benefits of technology

It realizes the preparation of ultra-white float glass in the existing float process, which meets the high transparency and gloss requirements of photovoltaic glass, and improves the mechanical strength and chemical stability of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a composition for glass, photovoltaic glass and a solar cell, and belongs to the technical field of solar cells. The composition for glass comprises 70%-73% of silicon dioxide, 0.5%-1.5% of aluminum oxide, 1%-3% of magnesium oxide, 9%-12% of calcium oxide, 0.006%-0.011% of iron oxide, 12%-15% of sodium oxide, 0.5%-1.5% of potassium oxide, 0.2%-0.5% of sulfur trioxide and 0.1%-1% of rare earth oxide, wherein the rare earth oxide comprises at least one of lanthanum oxide and ytterbium oxide; the rare earth oxide has a relatively high refractive index, and can form sulfate in the prepared glass after being matched with sulfur trioxide, so that the overall refractive index of the glass is further improved, the optical characteristics of the glass are improved, the effects of improving the transparency and glossiness of the glass are achieved, and the quality requirement of photovoltaic glass is met. And the preparation of the glass can be realized in the existing float process or calendering process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to a glass composition, photovoltaic glass, and a solar cell. Background Art

[0002] Photovoltaic glass is an essential material for photovoltaic modules, usually used as cover glass for crystalline silicon single-glass modules, cover and back glass for double-glass modules, and substrate glass for thin-film modules. The main function of photovoltaic glass in photovoltaic modules is to transmit light and protect the cells, so the basic requirements for photovoltaic glass are high light transmittance, high strength, and high durability.

[0003] The front glass of crystalline silicon photovoltaic modules has always been ultra-white patterned glass, but with the continuous development and progress of photovoltaic cell technology, a single ultra-white patterned glass can no longer meet the demand for photovoltaic glass for all photovoltaic modules. For example, with the development of monocrystalline PERC bifacial modules, and the rise of new TOPCon cells, heterojunction HJT cells and other technologies with higher bifacial rates, the proportion of double glass will become higher and higher, and the back glass will gradually use ordinary float glass and ultra-white float glass. In addition, with the development of the second-generation thin-film technology cadmium telluride and copper indium gallium selenide, as well as the development of the third-generation perovskite thin-film cells, the uniqueness of thin-film cells requires the use of ultra-white float glass.

[0004] However, the existing common float production lines are usually one kiln and one line, mainly producing large-size architectural glass with a thickness of 5-12mm, and the transmittance is low. The thickness of conventional photovoltaic glass is between 3.2mm and 2.0mm, and the glass transmittance is required to be above 91.6%. Therefore, even if the common float production line produces ultra-clear float glass, it cannot meet the quality requirements of photovoltaic glass. Summary of the invention

[0005] The present application provides a glass composition, photovoltaic glass, and solar cell, which can be used to prepare ultra-white float glass using a common float production line and can meet the quality requirements of photovoltaic glass.

[0006] In a first aspect, the present application provides a glass composition, wherein the components of the glass composition include, by mass fraction: 70%-73% silicon dioxide, 0.5%-1.5% aluminum oxide, 1%-3% magnesium oxide, 9%-12% calcium oxide, 0.006%-0.011% iron oxide, 12%-15% sodium oxide, 0.5%-1.5% potassium oxide, 0.2%-0.5% sulfur trioxide, and 0.1%-1% rare earth oxide, wherein the rare earth oxide includes at least one of lanthanum oxide and ytterbium oxide.

[0007] As an optional embodiment, the water content of lanthanum oxide is not more than 0.5%; and / or

[0008] The particle size of lanthanum oxide is no greater than 1 micron.

[0009] As an optional embodiment, the water content of ytterbium oxide is not more than 1%; and / or

[0010] The particle size of ytterbium oxide is no greater than 1 micron.

[0011] As an optional embodiment, in the glass composition, the total mass proportion of silicon dioxide and aluminum oxide is 71.5%-74%.

[0012] As an optional embodiment, in the glass composition, the total mass percentage of calcium oxide and magnesium oxide is 11%-14%.

[0013] As an optional embodiment, the glass composition further includes auxiliary materials, and the auxiliary materials include at least one of Glauber's salt, carbon powder, ammonium nitrate, cerium oxide or titanium oxide.

[0014] As an optional embodiment, in the glass composition, the mass percentage of Glauber's salt is 1%-3%; and / or

[0015] In the glass composition, the mass percentage of carbon powder is 0.1%-1%; and / or

[0016] In the glass composition, the mass percentage of ammonium nitrate is 0.1%-1%; and / or

[0017] In the glass composition, the mass percentage of cerium oxide is 0.1%-1%; and / or

[0018] In the composition for glass, the mass proportion of titanium oxide is 0.1% to 1%.

[0019] In a second aspect, the present application provides a photovoltaic glass, which is prepared using the glass composition provided in the first aspect.

[0020] As an optional implementation, when the thickness is 3 mm, the transmittance of the photovoltaic glass is ≥ 92% for light with a wavelength of 320 nm-1100 nm.

[0021] In a third aspect, the present application provides a solar cell, which includes the photovoltaic glass provided in the second aspect.

[0022] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0023] The glass composition provided in the embodiment of the present application, by selecting specific components, especially the combination and content selection of rare earth oxide and sulfur trioxide, the rare earth oxide itself has a high refractive index. After being combined with sulfur trioxide, sulfate can be formed in the manufactured glass, further improving the overall refractive index of the glass, thereby improving its optical properties, achieving the effect of improving the transparency and glossiness of the glass, and meeting the quality requirements of photovoltaic glass. At the same time, the glass composition can realize the preparation of glass in the existing float process or calendering process. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0025] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0026] An embodiment of the present application provides a glass composition, wherein the components of the glass composition include, by mass fraction, 70%-73% silicon dioxide, 0.5%-1.5% aluminum oxide, 1%-3% magnesium oxide, 9%-12% calcium oxide, 0.006%-0.011% iron oxide, 12%-15% sodium oxide, 0.5%-1.5% potassium oxide, 0.2%-0.5% sulfur trioxide, and 0.1%-1% rare earth oxide, wherein the rare earth oxide includes at least one of lanthanum oxide and ytterbium oxide.

[0027] In the present application, silicon dioxide (SiO2) forms an irregular continuous network structure with the structural unit of silicon-oxygen tetrahedron to form a glass skeleton. In addition, SiO2 can also increase the viscosity of the glass liquid, reduce the crystallization tendency of the glass, and improve the chemical stability and thermal stability of the glass, as well as the mechanical strength and transparency of the glass. When the SiO2 content is too high, it is easy to affect the transparency of the glass, and it is difficult to meet the transparency requirements of the ultra-white float photovoltaic glass. However, if the SiO2 content is too low, it will affect the strength of the glass, and it is also difficult to meet the mechanical strength requirements of the ultra-white float photovoltaic glass. Therefore, the content of SiO2 in the glass composition of the present application is controlled at 70%-73%.

[0028] In the present application, aluminum oxide (Al2O3) is in a tetrahedral structure in the glass, plays a role in repairing the network, can reduce the tendency of crystallization and the crystallization speed of the glass, reduce the expansion coefficient of the glass, and is an effective glass stabilizing component in the glass. However, too much Al2O3 will excessively increase the viscosity of the glass liquid, which is not conducive to the melting and clarification of the glass liquid and the generation of lines. Therefore, the Al2O3 content in the glass composition of the present application is preferably controlled at 0.5%-1.5%.

[0029] In the present application, magnesium oxide (MgO) belongs to a network intermediate oxide. Appropriate addition of magnesium oxide can reduce the high temperature viscosity of glass, reduce the crystallization tendency of glass, and optimize the comprehensive performance of glass. In addition, it can also inhibit the mold of photovoltaic glass. However, if the MgO content is too high, the viscosity of the glass liquid will increase. Therefore, the MgO content in the glass composition of the present application is controlled to be 1%-3%.

[0030] In the present application, calcium oxide (CaO) can reduce the viscosity of glass liquid under high temperature conditions, which is conducive to the melting and clarification of glass, and can increase the viscosity of glass liquid under low temperature conditions, which is conducive to the rapid molding of glass. However, too much CaO can easily increase the tendency of glass crystallization, making the glass brittle, more difficult to mold, poor impact resistance, and poor stability. Therefore, the CaO content in the glass composition of the present application is 9%-12%.

[0031] In the present application, iron oxide (Fe2O3) is not only the main colorant of float photovoltaic glass, but the content of Fe2O3 also affects the absorption of visible light by photovoltaic glass. Different valence states have different absorption of light. Trivalent iron ions mainly absorb ultraviolet light, while divalent iron ions mainly absorb visible light, which determines the energy conversion level of photovoltaic modules and is one of the key factors in measuring whether it can be used as a photovoltaic glass principle. When the Fe2O3 content is too high, greater than 0.011%, it will not only affect the transparency of photovoltaic glass, but also because it has a strong absorption effect on the thermal radiation of glass melting, it is easy to cause difficulty in convection of glass liquid in the melting furnace, increasing the difficulty of melting and clarification. Therefore, the Fe2O3 content in the glass composition of the present application is 0.006%-0.011%.

[0032] In addition, under the condition of a certain iron content, increasing the proportion of trivalent iron ions can reduce the degree of light absorption by iron ions, thereby improving light transmittance. By regulating the Fe2O3 content as mentioned above, ultra-white float photovoltaic glass can have a higher light transmittance, while reducing the difficulty of molding, achieving a balance between performance and molding process.

[0033] In the present application, sodium oxide (Na2O) is a metal oxide that can lower the melting temperature of glass, reduce the viscosity of glass liquid, and increase the high-temperature fluidity of glass liquid. It is a good flux. Too much Na2O content can easily cause the precipitation of sodium ions, causing the glass to precipitate alkali and mold, and the weather resistance of the glass to deteriorate. Therefore, the Na2O content in the glass composition of the present application is controlled at 12%-15%.

[0034] In the present application, potassium oxide (K2O) is also a metal oxide, which can produce a mixed alkali effect with Na2O, improve the glossiness of the glass, and reduce the precipitation of sodium ions on the glass surface, thereby improving the disadvantage of photovoltaic glass being prone to mold after long-term storage and improving the weather resistance of the glass. If the K2O content is too low, it will not be conducive to reducing the precipitation of sodium ions on the glass surface; if the K2O content is too high, the thermal expansion coefficient of the photovoltaic glass will increase, and the thermal shock resistance will decrease. Therefore, the K2O content in the glass composition of the present application is controlled at 0.5%-1.5%.

[0035] Sulfur trioxide (SO3) can exist in the form of a precursor (i.e., a substance that decomposes or reacts to sulfur trioxide during the glass preparation process), such as Glauber's salt, which can be oxidized and decomposed to generate sulfur trioxide. When sulfur trioxide exists as a precursor Glauber's salt, since Glauber's salt is also used as a clarifier for glass, if the amount of SO3 converted is too low, the glass will not be clarified well, resulting in bubbles that cannot be eliminated; if the amount of SO3 converted is too high, the amount of Glauber's salt is excessive, forming defects such as Glauber's salt bubbles. Therefore, the SO3 content in the glass composition of the present application is controlled at 0.2%-0.5%. The addition of lanthanum oxide can improve the transparency and glossiness of the glass, and has a significant effect on the radiation and scattering properties of light. At the same time, it can also improve the fluorescence properties of the glass, so that the glass has a better lighting effect at night. Lanthanum oxide can improve the chemical stability of the glass, making it more resistant to high temperatures, corrosion and durability, thereby extending the service life of the glass product. The main function of ytterbium oxide is to enhance the physical properties of glass. Ytterbium oxide can shorten the melting time of glass at high temperatures, making glass manufacturing more efficient. In addition, ytterbium oxide can enhance the heat resistance and corrosion resistance of glass, thereby increasing the service life of glass. Excessive addition of rare earth oxides will affect the preparation process, resulting in inapplicability to existing float or rolling processes. Therefore, the content of rare earth oxides in the glass composition of the present application is controlled at 0.1%-1%. Usually, the water content of rare earth oxides is not more than 0.5%, and the particle fineness of rare earth oxides is not more than 1 micron.

[0036] The glass composition selects specific components, especially the combination and content of rare earth oxide and sulfur trioxide. Rare earth oxide itself has a high refractive index. After being combined with sulfur trioxide, sulfate can be formed in the manufactured glass, further improving the overall refractive index of the glass, thereby improving its optical properties, achieving the effect of improving the transparency and glossiness of the glass, and meeting the quality requirements of photovoltaic glass. At the same time, the glass composition can realize the preparation of glass in the existing float process or calendering process.

[0037] In some embodiments, in the glass composition, the total mass percentage of silicon dioxide and aluminum oxide is 71.5%-74%. The total mass percentage of silicon dioxide and aluminum oxide is 71.5%-74%, within which the glass can achieve a high mechanical strength without causing a large burden on the melting and forming process. The melting process has a large burden, which easily affects the forming effect of the glass and then affects its thickness and light transmittance.

[0038] In some embodiments, in the glass composition, the total mass percentage of calcium oxide and magnesium oxide is 11%-14%. The total mass percentage of calcium oxide and magnesium oxide is 11%-14%, which can reduce the viscosity of the glass and achieve a better melting effect without generating a large number of crystallization defects that affect the light transmittance of the glass.

[0039] In some embodiments, the glass composition further includes auxiliary materials, and the auxiliary materials include at least one of Glauber's salt, carbon powder, ammonium nitrate, cerium oxide or titanium oxide. Further, in the glass composition, the mass proportion of Glauber's salt is 1%-3%; the mass proportion of carbon powder is 0.1%-1%; the mass proportion of ammonium nitrate is 0.1%-1%; the mass proportion of cerium oxide is 0.1%-1%; the mass proportion of titanium oxide is 0.1%-1%. By designing the auxiliary materials, the proportion of divalent iron in ultra-white float photovoltaic glass can be reduced, the proportion of trivalent iron can be increased, and the tin count in the glass can be reduced, so that the ultra-white float photovoltaic glass has a higher transmittance and flatness. Glauber's salt, as a glass clarifier, can achieve the purpose of clarifying the glass and improving the transmittance.

[0040] Based on a general inventive concept, an embodiment of the present application further provides a photovoltaic glass, which is prepared using the glass composition provided above.

[0041] Photovoltaic glass is also known as low-iron glass, ultra-white glass, etc. The industry standard "Glass for Solar Cells" defines it as glass with an iron content of no more than 150ppm, a visible light transmittance of ≥91.5% for a standard thickness of 3mm, and a direct transmittance of sunlight (spectral range of 300-2500nm) of 3mm standard thickness of ≥91%. Ultra-white glass is widely used in solar cell glass cover plates because it has a high transmittance within the spectral response range of solar cells (380-1200nm).

[0042] The photovoltaic glass is realized based on the above-mentioned glass composition. The specific content of the glass composition can be referred to the above-mentioned embodiments. Since the photovoltaic glass adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0043] In some embodiments, the preparation may be: heating the glass composition to 1500-1600° C. to melt, clarifying and cooling, using a float process or a calendering process to produce flat glass, and then annealing to obtain photovoltaic glass.

[0044] In the method, it is only necessary to mix the components according to the formula and heat and melt them, and no special equipment and environmental requirements are required. The preparation method is simple in process. The flat glass is obtained by the existing mature float process or calendering process, so that the final product yield is high. In addition, since the rare earth doping ratio is small, it does not affect the existing float process or calendering process, and only minor adjustments to the process parameters are required. Therefore, the preparation method is easy to operate and control and is suitable for industrial production.

[0045] Furthermore, the specific preparation process may be:

[0046] Step A1: preparing materials, preparing raw materials according to the proportion, and mixing the raw materials in proportion according to requirements to obtain a mixed material;

[0047] Specifically, step A1 includes:

[0048] Step A11: weighing, according to the mass proportion of each component in the mixture, and then pouring into the mixing device;

[0049] Step A12: Mixing, adding a grinding component to the mixing device, grinding the agglomerated raw materials during the mixing process, so as to improve the fineness of the mixture; wherein, the grinding component is provided with an electric heating component for heating and drying the mixture while grinding.

[0050] Step A13: Screening: The mixed material is screened through a sieve to remove impurities mixed in the raw materials and improve the purity of the mixture.

[0051] Step A2: Melting: feeding the mixed material into a melting furnace, heating the melting furnace, melting the mixed material at a high temperature to form molten glass, and the molten glass flows into a melting pool to keep the glass in a molten state;

[0052] Specifically, step A2 includes:

[0053] Step A21: feeding the mixed material into the furnace through the hopper;

[0054] Step A22: heating, starting the furnace and heating the mixture so that the mixture is fully melted in the furnace to form molten glass;

[0055] Step A23: Debubbling, using a stirring device to properly stir the molten glass to help bubbles gather and rise;

[0056] Step A24: Start the molten pool and preheat it, maintain the temperature of the molten pool, and allow the molten glass to flow into the molten pool to maintain the molten state of the glass.

[0057] Step A3: float forming, the molten glass flows from the melting furnace into the molten tin pool, the molten glass floats on the surface of the tin liquid and forms a flat glass plate;

[0058] Specifically, step A3 includes:

[0059] Step A31: start the molten tin pool in advance, heat and dissolve the tin into molten tin, adjust the temperature of the molten tin according to demand and maintain the temperature;

[0060] Step A32: adjusting the flow rate of the furnace outlet to increase or decrease the amount of glass poured into the tin pool, thereby controlling the final thickness;

[0061] Step A33: starting a nitrogen protection machine, and nitrogen forming a gas protection layer above the molten glass to protect the molten glass and polish it;

[0062] Step A34: The molten glass in the furnace flows into the molten tin pool. The molten glass floats on the surface of the molten tin and automatically unfolds into a uniform flat plate shape. The side pullers on both sides of the inner wall of the molten tin pool are used to promote the flow of the molten glass.

[0063] Step A4: Annealing: the float glass sheet enters the annealing furnace and is slowly cooled to eliminate internal stress;

[0064] Step A5: Cutting: using a laser cutting machine to cut the annealed glass sheet into the required size and shape, and performing edge polishing, punching and other processing on the cut glass according to processing requirements;

[0065] Step A6: coating, coating an anti-reflection coating on the surface of the glass plate.

[0066] In some embodiments, when the thickness is 3 mm, the transmittance of the photovoltaic glass for light with a wavelength of 320 nm-1100 nm is ≥ 92%.

[0067] Based on a general inventive concept, an embodiment of the present application further provides a solar cell, which includes the photovoltaic glass provided above.

[0068] The solar cell is realized based on the above-mentioned photovoltaic glass. The specific content of the photovoltaic glass can refer to the above-mentioned embodiments. Since the solar cell adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0069] In some embodiments, the photovoltaic glass can be used as the cover glass or back glass of a solar cell, or can be used as the substrate glass of a thin-film module, etc.

[0070] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0071] Examples and Comparative Examples

[0072] According to the glass composition shown in Table 1, the components in the examples and comparative examples were weighed and mixed, and the mixture was poured into a platinum crucible, and then heated in a high-temperature furnace at 1600°C for 7 hours, and stirred with a platinum rod to expel bubbles. The molten glass was poured into a stainless steel cast iron mold to form a specified block glass product, and then the glass product was annealed in an annealing furnace at 500°C for 1 hour, and the power was turned off and cooled to 25°C with the furnace. The glass product was cut, ground, and polished, and a 50×50×3mm glass intermediate sample was obtained by polishing.

[0073] Table 1

[0074]

[0075] The glass samples provided in each embodiment and comparative example were tested for performance, wherein the density ρ was measured using the Archimedean method; the thermal expansion coefficient α30 / 300 at 30-300°C was measured using a dilatometer (model: Orton DIL-2010) and expressed as the average expansion coefficient; the annealing point Ta (viscosity 10 13 dpa·s) and strain point Ts (viscosity 10 14.5 dpa·s) was measured using an Orton ANS-800 tester; the softening point Tf (viscosity 10 7.6 The viscosity was measured by Orton RSV-1600 cylindrical rotary high temperature viscometer, and the working temperature Tw (viscosity 10 dpa·s) was calculated by Fulcher (also known as VFT formula). 4dpa·s);Elastic modulus (also known as Young's modulus) was tested by resonance method (model: MHY-03481);Light transmittance was tested by UV-visible spectrophotometer (model: UV-2550), and the unit is %. The results are shown in Table 2.

[0076] Table 2

[0077]

[0078] As shown in Table 2, by using the glass composition provided in the embodiment of the present application, by selecting specific components, especially the combination and content of rare earth oxides and sulfur trioxide, the prepared glass sample meets the following requirements: 3mm standard thick glass 320-1100nm optical transmittance ≥ 92%, and other performance indicators meet the various performance requirements of photovoltaic glass for solar energy. Moreover, it can be prepared in the existing float process or calendering process, and can be promoted industrially.

[0079] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0080] In the description of the specification of the present application, the terms "include", "comprise", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple.

[0081] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A composition for glass, characterized in that: The components of the glass composition include, by mass fraction, 70%-73% silicon dioxide, 0.5%-1.5% aluminum oxide, 1%-3% magnesium oxide, 9%-12% calcium oxide, 0.006%-0.011% iron oxide, 12%-15% sodium oxide, 0.5%-1.5% potassium oxide, 0.2%-0.5% sulfur trioxide, and 0.1%-1% rare earth oxide, wherein the rare earth oxide includes at least one of lanthanum oxide and ytterbium oxide.

2. The glass composition according to claim 1, characterized in that The water content of the lanthanum oxide is not more than 0.5%; and / or The particle size of the lanthanum oxide is no greater than 1 micron.

3. The glass composition according to claim 1, characterized in that The moisture content of the ytterbium oxide is not greater than 1%; and / or The particle size of the ytterbium oxide is not greater than 1 micron.

4. The glass composition according to claim 1, characterized in that In the glass composition, the total mass proportion of the silicon dioxide and aluminum oxide is 71.5%-74%.

5. The glass composition according to claim 1, wherein In the glass composition, the total mass percentage of calcium oxide and magnesium oxide is 11%-14%.

6. The glass composition according to claim 1, characterized in that: The glass composition further comprises auxiliary materials, and the auxiliary materials comprise at least one of Glauber's salt, carbon powder, ammonium nitrate, cerium oxide or titanium oxide.

7. The glass composition according to claim 6, characterized in that: In the glass composition, the mass percentage of the sodium sulfate is 1%-3%; and / or In the glass composition, the carbon powder accounts for 0.1% to 1% by mass; and / or In the glass composition, the mass percentage of the ammonium nitrate is 0.1%-1%; and / or In the glass composition, the mass percentage of cerium oxide is 0.1%-1%; and / or In the glass composition, the mass proportion of the titanium oxide is 0.1%-1%.

8. A photovoltaic glass, characterized in that: The photovoltaic glass is prepared using the glass composition according to any one of claims 1 to 7.

9. The photovoltaic glass according to claim 8, characterized in that: When the thickness is 3 mm, the transmittance of the photovoltaic glass is ≥92% for light with a wavelength of 320 nm-1100 nm.

10. A solar cell, characterized in that: The solar cell comprises the photovoltaic glass according to any one of claims 8 to 9.